A lusofonia na mídia portuguesa, o caso da comemoração dos 500 anos brasileiros - de Renó Machado , Igor José (2002)
The article analyses how the Porcuguese media coverage about The "500 year" celebrations of Brazil expresses a vision about ir and, at the sarne time, builds up a nationalist discourse (Fox 1990). Focusing in April 2000, when the media coverage was more incense, It is illustrated how Lusophony has been disseminated in the Porcuguese press. The main objective is to understand the representations of Brazil and the Brazilians in Portugal and the link between renewed imperial discourse and the place where Brazil takes place. The arcicle shows a savage image labeled on Brazil in contrast to a supposed idea of "Porcuguese civilization".